Chapter Potential risk of gambling products and online gambling among European adolescents - Benedetti, Elisa (Proceedings e report, 2023)
he increased availability of gambling opportunities resulting from the progressive liberalisation of the gambling sector coupled with the widespread access to online gambling, is raising concerns regarding adolescents' participation in gambling and possible increase in problem-gambling. However, the influence of the different gambling products commercialised across countries is less known. This is the first study estimating problem gambling (PG) prevalence and examining the contribution of individual factors and gambling products on gambling engagement and PG development among European adolescents. The study used data from a representative cohort of 16-year-old students (n= 85,000) in 33 European countries participating in the 2019 ESPAD survey. In order to control for self-selection a Heckman probit model is estimated, first controlling for the probability of being gambler and then for the correlated probability of becoming a problem gambler. The influence of individual and country-level factors is estimated on both outcomes, as well as among gamblers using each type of gambling products. Participants who reported stronger family support had lower risk of gambling engagement, whilst friends' support, lack of school connectedness, low monitoring, higher parental education and access to money increased the risk. At the country-level, the higher diffusion of some gambling products was positively associated with gambling engagement. Once controlling for the influence on gambling engagement, factors that still increase the risk of becoming problem gambler independently from the country of origin were the lack of school connectedness and parental monitoring. Specific gambling products and online games increased PG risk. The influence of such factors on PG development is also analysed among gamblers using each product. Supportive family environments, school connectedness and limited access to money appear to be associated with a lower risk of PG among adolescents. At the country-level, governments should better enforce barriers to underage access to gambling products, particularly online.